2002
DOI: 10.1200/jco.2002.08.177
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Irinotecan Metabolism by Ketoconazole

Abstract: PURPOSE: Irinotecan (CPT-11) is a prodrug of SN-38 and has been registered for the treatment of advanced colorectal cancer. It is converted by the cytochrome P450 3A4 isozyme (CYP3A4) into several inactive metabolites, including 7-ethyl-10-[4-N-(5-aminopentanoic acid)-1-piperidino]-carbonyloxycamptothecin (APC). To investigate the role of CYP3A4 in irinotecan pharmacology, we evaluated the consequences of simultaneous treatment of irinotecan with a potent enzyme inhibitor, ketoconazole, in a group of cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 20 publications
8
55
1
1
Order By: Relevance
“…However, a possible explanation would be the fact that R115777 is known to inhibit CYP3A4 activity in human hepatic microsomal preparations, albeit at in vitro concentrations that are five-fold higher than the peak concentrations observed in the present study (Bohets, 1998). Previous investigations have shown that inhibition of CYP3A4 in patients on irinotecan treatment leads to shunting of parent drug to esterase-mediated hydrolysis to form SN-38 (Kehrer et al, 2002). The notion that the primary CYP3A4-mediated irinotecan metabolite APC is formed out of the carboxylate form of irinotecan (Xie et al, 2002), the pharmacokinetics of which are affected most, lends further support to a prominent role of CYP3A4 in the metabolism of irinotecan.…”
Section: Discussionmentioning
confidence: 75%
“…However, a possible explanation would be the fact that R115777 is known to inhibit CYP3A4 activity in human hepatic microsomal preparations, albeit at in vitro concentrations that are five-fold higher than the peak concentrations observed in the present study (Bohets, 1998). Previous investigations have shown that inhibition of CYP3A4 in patients on irinotecan treatment leads to shunting of parent drug to esterase-mediated hydrolysis to form SN-38 (Kehrer et al, 2002). The notion that the primary CYP3A4-mediated irinotecan metabolite APC is formed out of the carboxylate form of irinotecan (Xie et al, 2002), the pharmacokinetics of which are affected most, lends further support to a prominent role of CYP3A4 in the metabolism of irinotecan.…”
Section: Discussionmentioning
confidence: 75%
“…We retrospectively studied records from patients participating to various prospective clinical trials on CPT-11 in which pharmaco-kinetic monitoring was involved; the full clinical profiles are documented elsewhere (Kehrer et al, 2000(Kehrer et al, , 2001a(Kehrer et al, , 2002. All patients had a histologically or cytologically confirmed malignant solid tumour for which CPT-11 was considered to be a treatment option.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…It is a prodrug of the active metabolite, SN-38, and is converted by the CYP3A4 enzyme into several inactive metabolites. Recently, Kehrer et al demonstrated that concomitant administration of irinotecan with ketoconazole, an inhibitor of CYP3A4, causes alteration in the metabolism of irinotecan [156]. They showed that ketoconazole considerably increased the plasma concentrations of SN-38 as a result of inhibition of CYP3A4-mediated biotransformation.…”
Section: Modulation Of the Pharmacokinetics Of Irinotecanmentioning
confidence: 99%